A new settling velocity equation for cohesive sediment based on experimental analysis. Issue 2 (3rd July 2018) - Mhashhash, Aisha; Bockelmann-Evans, Bettina; Pan, Shunqi
Abstract: Cohesive sediment flocculates under particular circumstances, for example, the increase of salinity in the brackish zone of rivers, forming flocs that are larger and less dense than individual particles. The phenomenon of flocculation plays a significant role in the sediment transport processes of settling, deposition and erosion. This study used an extensive experimental setup using a particle image velocimetry (PIV) camera system to establish a new settling velocity equation as a function of salinity ( S ) and turbulence ( TS ). The results were compared with those of studies previously conducted at various estuaries. The experimental research was carried out in a 1 L glass beaker using suspended sediment samples from the Severn Estuary in the United Kingdom. A PIV system and an image processing routine were used to measure floc size distribution (FSD) and settling velocity. Based on the experimental data, Minitab was used to derive a new regression equation to predict the settling velocity.